Spatial and temporal genetic variation in Ethiopian barley (Hordeum vulgare L.) landraces as revealed by simple sequence repeat (SSR) markers - Allo A. Dido; Dawit T. Degefu; Ermias Assefa; M. S. R. Krishna; B. J. K. Singh; Kassahun Tesfaye (Agriculture & Food Security, 2021)
Abstract Background Ethiopia is considered as center of diversity for barley (Hordeum vulgare L.) and it is grown across different agro-ecologies of the country. Unraveling population structure and gene flow status on temporal scales assists an evaluation of the consequences of physical, demographic and overall environmental changes on the stability and persistence of populations. This study was to examine spatial and temporal genetic variation within and among barley landrace samples collected over a period of four decades, using simple sequence repeat markers. Results Results from STRUCTURE, neighbor joining tree and discriminant analysis of principal component (DAPC) analysis revealed presence low-to-high genetic diversity among the landraces and grouped the landraces into three clusters. The cluster analysis revealed a close relationship between landraces along geographic proximity with genetic distance increases along with geographic distance. From analysis of molecular variance (AMOVA) in terms of collection year, it was observed that within-population genetic diversity much higher than between population and that the temporal differentiation is considerably smaller. The low-to-high genetic differentiation between landraces could be attributed to gene flow across the region as a consequence of seed exchange among farmers. Conclusion The results demonstrate that this set of SSRs was highly informative and useful in generating a meaningful classification of barley germplasms. Furthermore, results obtained from this study also suggest that landraces are a source of valuable germplasm for sustainable agriculture in the context of future climate change and in situ conservation strategies following adaptation to local environments.